Pengaruh Atribut Produk dan Kepercayaan Merek Terhadap Minat Beli Produk Hp Vivo Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Nusa Nipa Maumere - Paulus Ariyanto Moa; Antonius Philipus Kurniawan; Walter Obon (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This research aimed to: (1) determine the description of product attributes, brandtrust and purchase interest: (2) analyze the significant influence of product attributes andbrand trust on purchase interest. The population in this research were students of the Faculty of Economics and Business, Nusa Nipa University, Maumere. The sample in this research was 96 respondents. Data were collected through questionnaires and analyzed using the descriptive inferential method, namely multiple linear regression. Hypothesis testing was carried out through the F test and test. The results of the descriptive analysis showed that the product attribute variables, brand trust and purchase interest were categorized as good. The results of the t-test statistics showed that the product attribute variables partially had a significant effect on the purchase interest variable, while the brand trust variable partially did not have a significant effect or the purchase interest variable. The results of the F-test statistics showed that both independent variables had a significant effect on the purchase interest variable. The results of the determination analysis show that the magnitude of the contribution of product atribut variables and brand trust to the purchase interest of Vivo cell phone products among students of the Faculty of Economics and Business, Nusa Nipa University Maumere is 22.9% while 77.1% is influenced by other factors outside the research variables.